Systematic Literature Review: Application of Augmented Reality to Improve Students' Creative Thinking Skills in Mathematics - Dewi, Christiana Kusuma; Waluya, Stevanus Budi (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
The problem in this Literature Review is to improve mathematical creative thinking skills through Augmented Reality. Creativity is a crucial skill to nurture in education, and mathematics plays a significant role in enhancing students' creative thinking abilities. Augmented Reality (AR) serves as a powerful educational tool, enabling educators to deliver information interactively and fostering creativity in students as they solve problems and address real-world scenarios. By utilizing AR as a medium for creative learning, it facilitates collaborative efforts among students and enhances their ability to think creatively. This study employs a Systematic Literature Review (SLR) method, analyzing seven journal articles that explore the use of AR in improving creative thinking skills within the context of mathematics education.